Predictors of Delayed Stroke in Patients with Cervical Artery Dissection. Issue 3 (April 2015) - Lichy, Christoph; Metso, Antti; Pezzini, Alessandro; Leys, Didier; Metso, Tiina; Lyrer, Philippe; Debette, Stéphanie; Thijs, Vincent; Abboud, Shérine; Kloss, Manja; Samson, Yves; Caso, Valeria; et al.
Background: Stroke in patients with acute cervical artery dissection may be anticipated by initial transient ischemic or nonischemic symptoms. Aim: Identifying risk factors for delayed stroke upon cervical artery dissection. Methods: Cervical artery dissection patients from the multicenter Cervical Artery Dissection and Ischemic Stroke Patients study were classified as patients without stroke ( n = 339), with stroke preceded by nonstroke symptoms (delayed stroke, n = 244), and with stroke at onset ( n = 382). Demographics, clinical, and vascular findings were compared between the three groups. Results: Patients with delayed stroke were more likely to present with occlusive cervical artery dissection ( P < 0·001), multiple cervical artery dissection ( P = 0·031), and vertebral artery dissection ( P < 0·001) than patients without stroke. No differences were observed in age, smoking, arterial hypertension, hypercholesterolemia, migraine, body mass index, infections during the last week, and trauma during the last month, but patients with delayed stroke had less often transient ischemic attack ( P < 0·001) and local signs (Horner syndrome and cranial nerve palsy; P < 0·001). Conclusions: Occlusive cervical artery dissection, multiple cervical artery dissection, and vertebral artery dissection were associated with an increased risk for delayed stroke. No other risk factors for delayed stroke were identified. Immediate cervical imaging of cervical artery dissection patients without ischemic stroke is needed to identify patients at increased risk for delayed ischemia.